The Level of Importance of Entrepreneurial Competencies according to Entrepreneurs and Scientists - Benedicta Prihatin Dwi Riyanti; Angela Oktavia Suryani; Christine Winstinindah Sandroto; Silverius Y Suharso (International Journal of Applied Business and International Management, 2020)
This study aimed to describe the rank of importance among 13 entrepreneurship competencies and the difference of the rank between entrepreneurs and scientists. About 47 entrepreneurs and 22 scientists gave their evaluation by giving rank from 1 to 13. The Mann-Whitney U-test showed that most of the competencies were perceived important at the same rank by the two groups, except for the competence of "Information seeking" (U-test = 722, p < 0.01; Mrank entrepreneurs = 6.36, Mrank scientist = 9.33). The top three competencies that perceived highly important by both groups are initiative, seeking and utilizing opportunities, and perseverance.